Dynamic Development of Fecal Microbiome During the Progression of Diabetes Mellitus in Zucker Diabetic Fatty Rats - Zhou, Wen; Xu, Huiying; Zhan, Libin; Lu, Xiaoguang; Zhang, Lijing (Frontiers in Microbiology, 2019)
Background: Although substantial efforts have been made to link the gut microbiota to type 2 diabetes, dynamic changes in the fecal microbiome under the pathological conditions of diabetes have not been investigated. Methods：Four male Zucker diabetic fatty (ZDF) rats were received Purina 5008 chow [protein=23.6%, Nitrogen-Free Extract(by difference)=50.3%, fiber(crude)=3.3%, ash=6.1%, fat(ether extract)=6.7%, and fat(acid hydrolysis)=8.1%] for 8 weeks. A total of 32 stool samples were collected from week 8 to week 15 in four rats. To decipher the microbial populations in these samples, we used a 16S rRNA gene sequencing approach. Results: Microbiome analysis showed that the changes in the fecal microbiome were associated with age and disease progression. In all the stages from 8 to 15 weeks of rats, phyla Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria primarily dominated the fecal microbiome. Although Lactobacillus and Turicibacter were the predominant genera in 8- to 10-week-old rats, Bifidobacterium, Lactobacillus, Ruminococcus, and Allobaculum were the most abundant genera in 15-week-old rats. Of interest, compared to the earlier weeks, relatively greater diversity (at the genus level) was observed at 10 weeks of age. Although the microbiome of 12-week-old rats had the maximum diversity, the diversity in 13–15-week-old rats was reduced. Spearman’s correlation analysis showed that F/B was negatively correlated with age. Random blood glucose was negatively correlated with Lactobacillus and Turicibacter but positively correlated with Ruminococcus and Allobaculum and Simpson’s diversity index. Conclusions: We demonstrated the time-dependent alterations of abundance and diversity of fecal microbiome during the progression of diabetes in ZDF rats. At the genus level, dynamic changes were observed. We believe that this work will enhance our understanding of the fecal microbiome development in ZDF rats and help to further analyze the role of the microbiome in metabolic diseases. Furthermore, our work may also provide an effective strategy for the clinical treatment of diabetes through microbial intervention.